Compatibility of Neem (Azadirachta indica) and Beauveria bassiana for Control of Spodoptera exigua and the Theoretical Impact to the Agroecosystem - Kurnianto, Agung Sih; Prastiwi, Santi; Dewi, Nilasari; Tanzil, Ahmad Ilham; Muhlison, Wildan; Wagiyana, Wagiyana (Biotropika: Journal of Tropical Biology, 2022)
Spodoptera exigua (Hubner) (Lepidoptera: Noctuidae) is the biggest threat to onion farming, especially in the vegetative phase. In severe attacks, this pest can cause yield losses of up to 100%. Compatibility is one way to increase the efficiency and effectiveness of pest control by using plant-based pesticides or biological agents. Neem Leaf Extract (Azadirachta indica, acronym=NLE) has an azadirachtin compound that can inhibit insect growth, reduce appetite, reproduction, and hatch eggs. The fungus Beauveria bassiana (acronym=Bb) can secrete chitinase, lipase, proteinase enzymes that are able to decompose insect cuticles. NLE was obtained through the extraction method of plant-based pesticides and stored at 4oC until the experiment time. The Bb used was a commercial B. bassiana inoculum in the flour form with a density of 4.5 x 1010 spores/gram (trade name = Natural BVR). To determine the advantages of compatibility, this study is held by a single toxicity test of Bb and NLE, and the combined toxicity test of both. This study used a completely randomized design (CRD) consisting of 6 treatments with 4 replications, each replication used 12 larvae (a total of 48 larvae). Combination toxicity has a higher toxicity than the single use of NLE and Bb. At the LC 95 level, the combination treatment of Bb and NLE was 1.06-1.15 times more toxic than the single treatment of Bb, and 6.87-7.79 times more toxic than the single treatment of NLE. NLE and Bb are considered to have high compatibility (strong synergistic with GI value <0.5). Theoretically, the compatibility of NLE plant-based pesticides and Bb is very promising to replace chemical pesticides that have long-term adverse effects on agroecosystems.